Mortality percentages related to heartwater and the economic impact of heartwater disease on large-scale commercial farms in Zimbabwe - Meltzer, M.I.; Perry, Brian D.; Donachie, P.L. (Elsevier, 1996)
A postal questionnaire asking for data concerning heartwater deaths was sent to all large-scale commercial farmers in Zimbabwe's lowveld, where heartwater is endemic. One hundred and fifty returns (24 percent return rate) provided usable data, with 85 farms (57 percent of sample) reporting heartwater deaths in 1990/91. The median heartwater mortality percentage for calves (0.12 months) was 2.3 percent. This was statistically significantly different (Wilcoxon signed rank test, P<0.005) from the median mortality percentage of 0.6 percent for cattle 13 months and older. Heartwater accounted for 51 percent of all mortalities on farms reporting heartwater deaths. There were no meaningful correlations between farm or herd size and heartwater mortality percentages. A plot of the farms reporting heartwater deaths found that the heartwater endemic area in 1991 is essentially unchanged from 1979. Inspection of the geographic distribution of farms reporting heartwater showed no obvious patterns, and distances from communal land farms were not significantly correlated to heartwater mortality percentages. An economic model found that the annual financial impact of heartwater on large-scale commercial farms in Zimbabwe to be some Z$19.4 million (1991 prices). The upper bound, that allowed for inflation since 1991, was Z$33.4 million. The lower bound estimate was Z$8.1 million (Z$3 = US$1, 1991 rates). Eighty-nine percent of these costs can be attributed to the cost of dipping. Since it has been shown experimentally that the carrier state of heartwater may not affect the productivity of cattle, intensive dipping may not be the best means of controlling heartwater.